(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Iron deficiency anemia (IDA) is a prevalent nutritional disorder, especially among women and children in developing countries. This study investigates the impact of nutrition, health, and hygiene counseling on the prevalence and management of iron deficiency anemia. Through a combination of dietary modifications, health education, and hygiene practices, the study aims to evaluate improvements in hemoglobin levels and overall health outcomes. Participants included women of reproductive age and children from a rural community, who were provided with structured counseling sessions over six months. Baseline and post-intervention data on hemoglobin levels, dietary intake, and hygiene practices were collected and analyzed. The results demonstrate significant improvements in hemoglobin levels and a reduction in the incidence of IDA, highlighting the effectiveness of comprehensive counseling as a sustainable intervention strategy.